Comparative efficacy of combined nebulized salbutamol with ipratropium bromide and nebulized adrenaline to treat children with acute bronchiolitis - Kadir, Md Abdul; Mollah, AH; Basak, R; Chowdhury, AM; Ahmed, S (Mymensingh Medical Journal, 2009)
Mymensingh Med J. 2009 Jul;18(2):208-14. The abstract of this article is available on the PubMed website